1990
DOI: 10.1161/01.str.21.6.874
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of right hemispheric cerebral infarction by hemicraniectomy.

Abstract: An anecdotal series of nine patients (three men and six women with an average age of 57 years) presented with progressive neurologic deterioration while on medical therapy for large right hemispheric cerebral infarction. Clinical signs of uncal herniation (anisocoria or fixed and dilated pupils, and/or left hemiplegia with right decerebrate posturing) were present in seven of these nine patients. Computerized tomography of the head confirmed mass effect from cerebral edema. It was the clinical judgment of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
3
9

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 17 publications
1
135
3
9
Order By: Relevance
“…24,27 A significant improvement in aphasia and a better overall outcome, however, have been observed with longer follow-ups. 5,16 Involvement of the dominant cerebral hemisphere should not preclude surgical decompression because long-term differences in clinical outcome after DH are not significantly different from those seen in patients with nondominant-hemisphere infarctions. 9,27,29 Intravenous tPA administration was not a significant predictor of poor outcome after DH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,27 A significant improvement in aphasia and a better overall outcome, however, have been observed with longer follow-ups. 5,16 Involvement of the dominant cerebral hemisphere should not preclude surgical decompression because long-term differences in clinical outcome after DH are not significantly different from those seen in patients with nondominant-hemisphere infarctions. 9,27,29 Intravenous tPA administration was not a significant predictor of poor outcome after DH.…”
Section: Discussionmentioning
confidence: 99%
“…The mRS ranges from 0 (no symptoms) to 6 (death), with intermediate values (1)(2)(3)(4)(5) representing increasing functional and cognitive disability. Poor functional outcome was defined as an mRS score of 4 (moderately severe disability), 5 (severe disability), or 6 (death).…”
Section: Outcomementioning
confidence: 99%
“…Historically, there has been reluctance to perform this operation because of a high rate of mortality and profound morbidity in survivors. Until recently, only case series and nonrandomized case-control studies suggested any benefit of decompressive craniectomy [39][40][41][42][43]. Several recent randomized controlled trials have demonstrated improved survival after decompressive craniectomy in certain stroke populations [6,[44][45][46].…”
Section: Osmotherapymentioning
confidence: 99%
“…The technique for decompressive haemicraniectomy is already well established 10,11 . It includes the A B remotion of a large (≥ 12 cm) bone flap with a circular or oval shape including the frontal, parietal, temporal and parts of the occipital squamae (with special care to avoid producing sharp bone edges); fixation of the dura at the edge of the craniectomy to prevent epidural bleeding; opening of the dura (usually one longitudinal and three radial incisions almost reaching the osseous rim) and placement of a dural patch made of lyophilised cadaver dura or more recently microporic poliester-uretane (Neuro-Patch ® ) in the incision.…”
Section: Discussionmentioning
confidence: 99%